AeU Offers Festive Special fees for Two Online Programmes. - Borneo, Post (Borneo Post, 2018)
Asia e University (AeU) is offering a Festive Special Fees for an Online MEd programme at RM11.880 for the online MBA programm. Through Accreditation of Prior Experiential learning (APEL), working adults can now attain recognition for thier work experience and life skills for the purpose of admission into institutions of higher learning